Genetic engineering - Russo, Enzo (Oxford University Press, 2000)
What is genetic engineering? How is it carried out and what can it do? What is cancer and can genetic engineering provide a cure? Why is AIDS so difficult to cure? Which diseases are determined genetically, and how are they passed on from parents to their children? Is intelligence genetically determined? Can gene therapy cure all our genetic diseases? Can genetic engineering solve the problem of world famine? Are genetically-engineered organisms a threat to the Earth's ecology? Should people be discriminated against by insurance companies and employers because of their genes...